Becoming a Thai National Female Leader on a Successful Path - Silpasuwan, Pimpan; Rodcumdee, Branom; Rerksngarm, Anchalee; Udchumpisai, Monthira; Saleekul, Sumlee; Tongvichean, Sulee; Poopongpan, Woraporn; Putthikhan, Phawida (The journal of values based leadership, 2021)
This study was configured to examine one Thai leader's life history and work, namely Major General Lady Asa nee Saovapap. At a time when female leadership throughout the world in key governmental and business levels of leadership has begun to show potential for steady growth, studies of individual female heads are particularly noteworthy, especially in countries with ever-changing government types - be it a parliamentary system, a military junta, a nascent democracy, or a constitutional monarchy. The method selected for this study largely involved autobiographical and biographical research. The data was derived from the subject's self-recorded history and accountings of her closest associates. In all, 29 key informants were interviewed during 2019-2020 for this study, employing different question sets. The empirical data's trustworthiness was thoroughly cross-checked for reliability. The outcomes of this research overwhelmingly portray the subject as an exemplary figure who converted formidable challenges into life and career-building opportunities, bettering society overall in the process.